EU citizenship and the member states’ own competence regulating the conditions of obtaining or forfeiting national citizenship - Pączek, Marcin (The Opole Studies in Administration and Law, 2020)
The ability of a state to decide freely on the conditions of obtaining or forfeiting its national citizenship has always been perceived as a core element of sovereignty. Within the legal framework of the EU, the member states have remained competent to regulate the question of who qualifies as a national. However, taking into account that EU citizenship is founded on citizenships of the member states, it is incumbent on them to determine who is to be classified as an EU citizen and consequently, who can enjoy the accompanying rights. The purpose of this paper is to investigate the degree to which the member states’ competence to regulate nationality matters has been affected by the introduction of EU citizenship.